PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN PENDEKATAN SAINTIFIK BERBASIS TPACK TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN LITERASI MATEMATIKA SISWA SMA - Marliani, Depi; Haji, Saleh; Hanifah, Hanifah (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The aim of this research is: 1) to determine the effect of the Problem Based Learning (PBL) learning model with a TPACK-based scientific approach on students' problem solving abilities. 2) To determine the effect of the Problem Based Learning (PBL) learning model with a TPACK-based scientific approach on students' mathematical literacy abilities. The type of research used is quasi-experimental design. This research was carried out at SMA Negeri 1 Empat Lawang with a population of 138 students in class XI Science. The research sample was students of class XI IPA 1 as a control class, totaling 34 students and class The research results show that: 1). There are differences in problem solving abilities between students taught using the Problem Based Learning learning model with a TPACK-based Scientific Approach and conventional learning after controlling for students' initial abilities, namely a sig value < 0.001. 2). There is a difference in mathematical literacy abilities between students taught using the Problem Based Learning learning model with a TPACK-based Scientific Approach and conventional learning after controlling for students' initial abilities, namely a sig value < 0.001. 3.) there is a linear influence of the covariate of students' initial problem solving ability on the final problem solving ability of students who are taught through the Problem Based Learning learning model with a TPACK-based scientific approach with a si value of <0.001. 4). There is a linear influence of the covariate of initial mathematical literacy ability on the final mathematical literacy ability of students taught through the Problem Based Learning learning model with a TPACK-based scientific approach, with a sig value <0.001.